Disease-associated nonsense and frame-shift variants resulting in the truncation of the GluN2A or GluN2B C-terminal domain decrease NMDAR surface expression and reduce potentiating effects of neurosteroids - Kysilov, Bohdan; Kuchtiak, Viktor; Hrcka Krausova, Barbora; Balik, Ales; Korinek, Miloslav; Fili, Klevinda; Dobrovolski, Mark; Abramova, Vera; Chodounska, Hana; Kudova, Eva; Bozikova, Paulina; Cerny, Jiri; et al. (Cellular and molecular life sciences, 2024)
N-methyl-D-aspartate receptors (NMDARs) play a critical role in normal brain function, and variants in genes encoding NMDAR subunits have been described in individuals with various neuropsychiatric disorders. We have used whole-cell patch-clamp electrophysiology, fluorescence microscopy and in-silico modeling to explore the functional consequences of disease-associated nonsense and frame-shift variants resulting in the truncation of GluN2A or GluN2B C-terminal domain (CTD). This study characterizes variant NMDARs and shows their reduced surface expression and synaptic localization, altered agonist affinity, increased desensitization, and reduced probability of channel opening. We also show that naturally occurring and synthetic steroids pregnenolone sulfate and epipregnanolone butanoic acid, respectively, enhance NMDAR function in a way that is dependent on the length of the truncated CTD and, further, is steroid-specific, GluN2A/B subunit-specific, and GluN1 splice variant-specific. Adding to the previously described effects of disease-associated NMDAR variants on the receptor biogenesis and function, our results improve the understanding of the molecular consequences of NMDAR CTD truncations and provide an opportunity for the development of new therapeutic neurosteroid-based ligands.
Keywords: elektrofyziologické jevy; Glutamate receptors; Neurosteroids; Rescue pharmacology; Electrophysiological Phenomena; GRIN2 genes; Surface expression; lidé; Channelopathy; Receptors, N-Methyl-D-Aspartate; receptory N-methyl-D-aspartátu; Humans; neurosteroidy; Endogenous neuroactive steroid